Endangering The Lives And Physical Integrity Of Others In The Penal Code (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The human right to life and physical integrity was one of the most important rights that the Penal Code seeks to protect, so its criminalization is not limited to acts that cause actual harm to this right, but has expanded the scope of protection by criminalizing acts that threaten this right. In order to achieve this goal, the Syrian Penal Code contained many legal provisions that seek to protect this right from endangerment, which can be summed up in crimes of mass danger on the one hand, and crimes of endangering the child and the disabled on the other, but the Syrian legislature has not followed the approach of other legislation based on the criminalization of any act that would endanger the right to life and physical integrity of others.Based on the above, this research highlights the scattered texts contained in the Syrian Penal Code aimed at protecting the right of others to life and physical integrity from endangerment, with the aim of examining their effectiveness and examining how to avoid their shortcomings, and then examining the approach adopted by the comparative law, which shows the approach of general criminalization of each act that endangers this right in order to take advantage of these laws to achieve the desired protection